(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
It is a prospective study of 65 road traffic injury cases admitted in M.A.P.I.M.S., which is a tertiary health care centre from January 2010 to December 2011. In the present study, male victims (54 cases, 83%) outnumbered the female victims (11 cases, 17%) with an approximate male-female ratio of 5:1. Four wheelers and two wheelers involving mainly pedestrians were the most common cause for fatal head injury seen in 43 cases, 66% cases. Multiple abrasions were the most commonly seen external injury seen in 58 cases, 89% cases. Skull bone fracture was seen in 26 cases, 40% cases. Temporal and parietal bones were the common site of fracture seen in 27 cases, 41% cases. The mean survival period was 73.42 hours, range being 6 hours to 600 hours.